Determining the top research priorities in UK prehospital critical care: a modified Delphi study. Issue 4 (17th January 2023) - Ramage, Lisa; McLachlan, Sarah; Williams, Kristian
Abstract : Background: Prehospital critical care is a rapidly evolving field. There is a paucity of evidence relating to its practice, with limited progress in answering those research questions identified over a decade ago. It is vital that evidence gaps are identified and addressed. This study aimed to define the current research priorities in UK prehospital critical care. Methods: This modified national Delphi study was coordinated by the Pre-HOspital Trainee Operated research Network and conducted in four rounds between October 2021 and April 2022. Rounds 1 and 2 were conducted online with clinicians involved in prehospital critical care delivery and non-clinical prehospital researchers. Rounds 3 and 4 were completed online by a subject matter expert (SME) panel. Results: In round 1, 78 participants submitted 394 research questions relating to prehospital critical care delivery in the UK. These were refined and categorised into 192 questions, which were scored for importance in round 2. Fifty questions were discussed and scored by the SME panel in round 3. Round 4 created a ranked top 20 list. The top research priority was 'Which cardiac arrest patients should critical care teams be dispatched to; how do we identify these patients during the emergency call?'. Other priorities included dispatch optimisation, out-of-hospital medical cardiac arrest management, optimising resuscitation in haemorrhagic shock, improving traumatic brain injury outcomes and optimising management of traumatic cardiac arrest. Conclusions: This modified Delphi study identified 20 research priorities where efforts should be concentrated to develop collaborative prehospital critical care research within the UK over the next 5 years.